Oriental macropterous leaf-mimic pygmy grasshoppers—genera Oxyphyllum and Paraphyllum (Orthoptera: Tetrigidae) and their taxonomic assignment - Skejo, Josip; Gupta, Sunil Kumar; Chandra, Kailash; Panhwar, Waheed Ali; Franjević, Damjan (Zootaxa, 2019)
There are numerous pygmy grasshoppers (Tetrigidae) that exhibit leaf-like appearance. Leaf-mimic species can be found mainly in the subfamily Cladonotinae (tribes Cladonotini, Xerophyllini). Two leaf-mimic pygmy grasshopper species found in India, Pakistan (Oxyphyllum pennatum Hancock, 1909) and Borneo (Paraphyllum antennatum Hancock, 1913) are the only macropterous leaf-like species of Asia and were traditionally assigned to subfamily Cladonotinae. Our study present new records of these species, as well as updated descriptions. Oxyphyllum pennatum is recorded for the first time from Chhattisgarh (Central India), and furthermore, records from Pakistan were reviewed and confirmed. Paraphyllum antennatum is reported from a few localities in the mountains of Borneo (East Malaysia). New records found in online social media (Flickr, iNaturalist) were implemented. Brachypronotal specimens of P. antennatum are reported. After comparison with Cladonotini and Xerophyllini members, we conclude that Oxyphyllum and Paraphyllum should not be regarded Cladonotinae members. Traditional assignment was based on superficial resemblance to leaf-like Cladonotinae genera (e.g. Phyllotettix, Hymenotes, Holoarcus, Xerophyllum). However, comparison of morphological characters reveals that Oxyphyllum shares morphology with Tetriginae genera, while Paraphyllum shares morphology with Asian Metrodorinae. Here, we assign the genus Oxyphyllum to Tetriginae and the genus Paraphyllum to Metrodorinae.